Associated factors with organizational communication among physiotherapy service professionals in the private sector - Valles-Tapia, Antonio (2024)
Objective: To determine the associated factors of organizational communication among health personnel in the physiotherapy department of a private clinic in Lima, Peru. Methods: The research was non-experimental, quantitative, observational, and analytical. The sample was census-based and consisted of 100 healthcare professionals. Information was collected using a questionnaire segmented by sociodemographic and work-related factors, in addition to the organizational communication questionnaire from Portugal; in the same way, the Chi-square test was applied. Results: No factor was found to be signifcantly associated with organizational communication, as the p-value was greater than 0.05. However, personnel withhigh organizational communication were mostly between the ages of 18 and 29 (56.7%), 59.3%were male, and 72.7% were medical doctors, compared to those with medium or low levelsof organizational communication. Conclusions: No factor was signifcantly associated with a high level of organizational communication among the hysiotherapy service professionals.